A case of non-small cell lung cancer presenting anti-amphiphysin antibody-positive paraneoplastic neurological syndrome. (2021) - Nakashima, Koki; Fujii, Yuya; Sato, Masayuki; Igarashi, Kazunari; Kobayashi, Motohiro; Ishizuka, Tamotsu
Abstract: Paraneoplastic neurological syndrome (PNS) is associated with malignancies, such as small-cell lung cancer. However, patients with non-small cell lung cancer (NSCLC) rarely develop PNS. We herein report a 72-year-old man with NSCLC who developed disturbance of consciousness on the day of initiation of treatment with an immune checkpoint inhibitor. Blood test results revealed anti -amphiphysin (AMPH) antibody positively, leading to the diagnosis of PNS. The disturbance of consciousness was improved with intravenous administration of steroid and immunoglobulin. To our knowledge, this is the first report of anti -AMPH antibody-positive PNS in a patient with NSCLC.